2011
DOI: 10.1002/adsc.201000887
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isoquinolines via Rhodium(III)‐Catalyzed Dehydrative CC and CN Coupling between Oximines and Alkynes

Abstract: Isoquinolines have been synthesized from the redox-neutral dehydrative C À N and C À C crosscoupling between oximines and alkynes using a catalytic amount of (pentamethylcyclopentadiene)rhodium dichloride dimer {[RhCp*Cl 2 ] 2 } and cesium acetate (CsOAc), a process that involves ortho C À H activation of oximines and subsequent functionalization with alkynes. This redox-neutral catalytic isoquinoline synthesis operates under mild conditions, and is insensitive to moisture or air. A broad scope of coupling par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
70
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(72 citation statements)
references
References 48 publications
1
70
0
1
Order By: Relevance
“…1 This concept has been extensively explored in the Rh(III) catalyzed synthesis of nitrogen containing heterocycles mediated by C–H activation. 2 A wide swath of unsaturated heterocycles can be accessed though coupling amides, amines, oximes, and anilines with alkynes to access isoquinolones, 3 pyridones, 3d,4 isoquinolines, 5 pyridines, 5g,6 indoles, 7 and pyrroles. 7b,8 …”
mentioning
confidence: 99%
“…1 This concept has been extensively explored in the Rh(III) catalyzed synthesis of nitrogen containing heterocycles mediated by C–H activation. 2 A wide swath of unsaturated heterocycles can be accessed though coupling amides, amines, oximes, and anilines with alkynes to access isoquinolones, 3 pyridones, 3d,4 isoquinolines, 5 pyridines, 5g,6 indoles, 7 and pyrroles. 7b,8 …”
mentioning
confidence: 99%
“…16-17 However, we found that the nucleophilic alcoholic solvents utilized in their protocols, MeOH or 2,2,2-trifluoroethanol (TFE), posed a problem for the construction of fluorinated analogues due to alcohol displacement of the fluorine under the basic reaction conditions (Table 1, entries 1–2). To avoid fluoride displacement we examined a range of nonhydroxylic solvents, and while most proved to be ineffective (see Table S1 in the SI), ethyl acetate resulted in complete conversion to fluoropyridine 3a with minimal byproduct formation as determined by 19 F NMR (entry 3).…”
mentioning
confidence: 99%
“…In 2010, Chiba described a rhodium-catalyzed synthesis of isoquinolines from ketone Oacyloximes and internal alkynes with the use of NaOAc as an effective additive and an external co-oxidant was not needed. 7 Later, Li reported the use of oxime as directing group and CsOAc as the additive also leading to the rapid formation of isoquniolines. 7 The oximes have been thought as oxidizing-directing groups during the rhodium-catalyzed procedures.…”
mentioning
confidence: 99%
“…7 Later, Li reported the use of oxime as directing group and CsOAc as the additive also leading to the rapid formation of isoquniolines. 7 The oximes have been thought as oxidizing-directing groups during the rhodium-catalyzed procedures. By replacing the rhodium catalysts with ruthenium complexes, Jeganmohan 8 and Ackermann 9 independently realized the synthesis of isoquinolines synthesize isoquinolines.…”
mentioning
confidence: 99%